Glyptothorax coracinus, a new species of hillstream catfish from Cambodia (Teleostei: Sisoridae) - Ng, Heok Hee; Rainboth, Walter J. (Zootaxa, 2008)
Glyptothorax coracinus sp. nov. is described from the western face of the Krâvanh (Cardamom) Mountains and Dâmrei (Elephant) Mountains in southwestern Cambodia. It can be distinguished from congeners by its color pattern consisting of blackish brown body with indistinct pale longitudinal stripes on the lateral line and mid-dorsal regions of the body, pale markings on the nuchal plate absent, length of adipose-fin base 12.3–14.5% SL, length of caudal peduncle 18.6– 21.0% SL, depth of caudal peduncle 7.9–9.4% SL, body depth at anus 11.0–14.6% SL, eye diameter 6.3–7.2% HL, 36– 37 vertebrae, tubercles on the dorsal surface of the head with a single, median ridge, and anastomosing striae absent on thoracic adhesive apparatus that does not reach the level of the base of the last pectoral-fin ray.